REFORMULASI KEBIJAKAN PEMIDANAAN TERHADAP DELIK TERKAIT EUTHANASIA DALAM RANGKA PEMBAHARUAN HUKUM PIDANA NASIONAL - Rionardo Farlus Patitan; Ade Adhari (Jurnal Hukum Adigama, 2021)
Humans have the right to live and in terms of the right to live there is the right to die which is internationally recognized by the United Nations so that an act appears to stop someone's life, namely Euthanasia. Along with the problems that arise regarding Euthanasia, a sanction is needed in which to deal with the problems that occur, especially in criminal matters. Euthanasia is often encountered and becomes a problem for people who experience it because in other countries Euthanasia is allowed by the government. This is based on various cases in various countries. The government must give strict sanctions to the perpetrators of Euthanasia but in general, in this aspect, criminal law policies in Indonesia are still inadequate and not appropriate in imposing sentences so that a policy of formulation of punishment for Euthanasia offenses in Indonesia needs to be carried out. The writing of this thesis uses doctrinal legal research methods and uses doctrines as supporting data. The results of the study reveal that sanctions against Euthanasia cases have not yet been able to be carried out by the Government because there is no clarity and legal certainty in Indonesia so that it is necessary to formulate a sentence for the Euthanasia offense.